2017
DOI: 10.12669/pjms.334.13143
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Expression of Topo IIα and Ki67 in Breast Cancer and its clinical Pathological characteristics

Abstract: Objective:To investigate the expression of Topo IIα and Ki67 and its clinical significance.Methods:The clinical pathological data of one hundred and sixteen invasive breast cancer patients who were admitted into our hospital from July 2013 to December 2015 and underwent radical mastectomy were retrospectively analyzed. The expression of topoisomerase (Topo) IIα and Ki67 was detected using immunohistochemical method, and the correlation between the two kinds of proteins and the general clinical pathological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The expression level increases gradually with the development of the disease. The results of this study showed that the positive expression rate of Ki67 in breast cancer tissues was significantly higher than that in adjacent tissues and the positive rate of Ki67 was related to tumor diameter and lymphatic metastasis of breast cancer (P<0.05), and the multi-factor logistic regression analysis suggested that lymphatic metastasis was the independent predictive indicator of positive expression of Ki67, which was consistent with most previous studies,16,17 It suggested that the positive expression of Ki67 was closely related to the growth, invasion and lymphatic metastasis of breast cancer and that the proliferation of breast cancer cells was active, Ki67-positive tumor cell grew fast and had high invasion and poor prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…The expression level increases gradually with the development of the disease. The results of this study showed that the positive expression rate of Ki67 in breast cancer tissues was significantly higher than that in adjacent tissues and the positive rate of Ki67 was related to tumor diameter and lymphatic metastasis of breast cancer (P<0.05), and the multi-factor logistic regression analysis suggested that lymphatic metastasis was the independent predictive indicator of positive expression of Ki67, which was consistent with most previous studies,16,17 It suggested that the positive expression of Ki67 was closely related to the growth, invasion and lymphatic metastasis of breast cancer and that the proliferation of breast cancer cells was active, Ki67-positive tumor cell grew fast and had high invasion and poor prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…Mean harvested lymph node number in axillary dissection was 15 (range [13][14][15][16][17]. Axillary status was negative in 141 (47.3%) patients and positive in 157 patients (52.7%).…”
Section: Resultsmentioning
confidence: 99%
“…It entered clinical use in 2011 St. Gallen International Expert Consensus on the Primary Therapy of Early BC [15]. In the study of Jin et al [16], they concluded that Topo II α and Ki-67 expression were well correlated with the number of metastatic lymph nodes. So, that the positive expression of Ki-67 in BC tissues can be regarded as a determinant for prognosis.…”
Section: Discussionmentioning
confidence: 99%